Prediction of water leakage in pipeline etworks using graph convolutional network method - (:unkn) unknown (My University, 2023)
Featured Application: Considering the theoretical contribution of the study to science, the use of graphs in monitoring leaks in pipelines and the application of graph-based machine learning for detection represent a novel approach in the literature. The datasets generated in this study will be made available to other scientists, serving as a foundation for further research and offering various benefits. When assessing the impact of this work on social life, it becomes crucial to utilize water resources effectively and efficiently due to increasing demand resulting from both global warming and urbanization. Ensuring the sustainability of our world heavily relies on this aspect. This study aims to predict leaks in water-carrying pipelines by monitoring pressure drops. Timely detection of leaks is crucial for prompt intervention and repair efforts. In this research, we represent the network structure of pipelines using graph representations. Consequently, we propose a machine learning model called Graph Convolutional Neural Network (GCN) that leverages graph-type data structures for leak prediction. Conventional machine learning models often overlook the dependencies between nodes and edges in graph structures, which are critical in complex systems like pipelines. GCN offers an advantage in capturing the intricate relationships among connections in pipelines. To assess the predictive performance of our proposed GCN model, we compare it against the Support Vector Machine (SVM) model, a widely used traditional machine learning approach. In this study, we conducted experimental studies to collect the required pressure and flow data to train the GCN and SVM models. The obtained results were visualized and analyzed to evaluate their respective performances. The GCN model achieved a performance rate of 94%, while the SVM model achieved 87%. These results demonstrated the potential of the GCN model in accurately detecting water leaks in pipeline systems. The findings hold significant implications for water resource management and environmental protection. The knowledge acquired from this study can serve as a foundation for predicting leaks in pipelines that transport gas and oil.
Keywords: Bilgisayar Bilimleri; Kimya Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Computer Sciences; Chemical Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; Malzeme Bilimi; ALETLER & GÖSTERİM; MÜHENDİSLİK, KİMYASAL; KİMYA, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; INSTRUMENTS & INSTRUMENTATION; ENGINEERING, CHEMICAL; CHEMISTRY, APPLIED; Genel Malzeme Bilimi; Fizik Bilimleri; Enstrümantasyon; Genel Mühendislik; Proses Kimyası ve Teknolojisi; Bilgisayar Bilimi Uygulamaları; Akışkan Akışı ve Transfer İşlemleri; General Materials Science; Physical Sciences; Instrumentation; General Engineering; Process Chemistry and Technology; Computer Science Applications; Fluid Flow and Transfer Processes; graph convolutional network; graph machine learning; leakage detection